The Implementation of Traditional Indonesian Snack Creations as Entrepreneurship Learning Media at PGRI University of Palembang - Pratiwi, Nova; Januardi (Technium Social Sciences Journal, 2020)
This research seeks to provide a meaningful entrepreneurship learning experience for students, and to increase cultural literacy, especially concerning traditional snacks among students, the millennial generation with the tendency of showing antipathy to traditional snacks. This research used a qualitative design with data collection techniques of documentation, questionnaires, and interviews. The informants were students of the Elementary School Teacher Education study program at PGRI University of Palembang who attended entrepreneurship course, amounted to 36 students. The research results showed that the implementation of learning media in the form of traditional Indonesian snack creations has provided opportunities for students to gain valuable lessons that they might not have obtained in entrepreneurship learning through theory and discussion in the classroom, the entrepreneurial activities ran well which more than 80% of students made a profit in their entrepreneurial activities, and the students’ entrepreneurship learning outcomes increased in line with the implementation of learning media of traditional Indonesian snack creations.